2019
DOI: 10.4014/mbl.1808.08011
|View full text |Cite
|
Sign up to set email alerts
|

Cultivable Microbial Diversity in Domestic Bentonites and Their Hydrolytic Enzyme Production

Abstract: Clay minerals are classified as kaolinite and montmorillonite minerals, as a class of layered silicates formed from chemical weathering of other silicate minerals on the surface of the earth [1]. Clay minerals with varying amounts of iron, magnesium, alkali metals, alkaline earths, and other cations are present in the interlayer space or in the lattice structure. They have well-known adsorbent properties due to their layered form, with a high internal surface area, high cation-exchange capacity, and good swell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…was isolated in the soil [16]. Taken together with previous studies, our results showed a high microbial diversity in bentonite and zeolite samples, dominated by bacterial phyla Firmicutes and Actinobacteria [15,19,20]. Cultivable isolation of diverse microorganisms from clay minerals triggered the investigation of industrial enzyme productions to promote the industrial application of clay minerals-derived functional microorganisms.…”
supporting
confidence: 73%
See 3 more Smart Citations
“…was isolated in the soil [16]. Taken together with previous studies, our results showed a high microbial diversity in bentonite and zeolite samples, dominated by bacterial phyla Firmicutes and Actinobacteria [15,19,20]. Cultivable isolation of diverse microorganisms from clay minerals triggered the investigation of industrial enzyme productions to promote the industrial application of clay minerals-derived functional microorganisms.…”
supporting
confidence: 73%
“…B. amyloliquefaciens DL-3 and B. licheniformis CDB-12 [25,26]. Our previous study also reported that 30 strains isolated from bentonite samples showed cellulase activity, including B. tequilensis MBLB1223 and B. siamensis MBLB1268 [20]. Pectinase responsible for the degradation of pectin polysaccharides are industrially useful enzyme for the clarification, extraction and concentration of tea and juice as well as textile fibre production [27].…”
mentioning
confidence: 93%
See 2 more Smart Citations